Shaping A Public Opinion As A Political Communication Challenge In Digital Disruption Era - Andri Kurniawan; Fadilah Thunisyah Hasyanah; Dwi Khatami Darmawan (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
The image of political actors and political parties is deemed good or bad when obtained by rising public opinion. Political communication skills are a difficulty, especially in the middle of digital disruption era. This research employs a qualitative method with a literature analysis. The result of the research is that public opinion is produced from the consumption of speech that is witnessed, including the political concerns they witness. The importance of preserving public opinion is a prerequisite for political actors and political parties to attain a common vision and objective. This has been demonstrated by public opinion, which believes that the president of the Republic of Indonesia, Joko Widodo, is rumored to be a communist. Public opinion is like a wild ball; if it is not managed, it will be harmful. The case turned out to be not only fake news because it was not founded on empirical facts, but it was also suspected that the matter was rolling because of political objectives.